Penanganan Hipotiroid pada Anak dengan Sindrom Nefrotik - Bernadetha Nadeak (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
Hypothyroid or thyroid hormone deficiency is a state of hormone deficiency due to the thyroid gland not being able to produce sufficient amounts. This hypothyroid is a complication that often occurs in nephrotic syndrome, but often does not show clinical symptoms. Hypothyroid in nephrotic syndrome occurs due to the release of thyroid hormone and thyroxin-binding globulin (TBG) through urine which will reduce the concentration of free thyroid hormone and increase thyroid stimulating hormone (TSH). The purpose of writing this article is to find out how to manage hypothyroid in children with nephrotic syndrome. The method used in this paper is qualitative research with a